Up-regulation of erythropoietin receptor by nitric oxide mediates hypoxia preconditioning - Zhi Yong Chen (2018)
Erythropoietin (Epo), known to stimulate erythroid progenitor cell survival, proliferation, and differentiation, has been shown to be neuroprotective against brain ischemia in animal models. Both Epo and Epo receptor (EpoR) are expressed in the brain and are up-regulated by hypoxia. Brain Epo signaling can stimulate neural cell survival and prevent neuron apoptosis. Neurons from EpoR null mice exhibit marked increased sensitivity to hypoxia. In endothelial cells, Epo has been shown to stimulate nitric oxide (NO) production, particularly at low pO2. We found here that the EpoR expression on neural cells and Epo's neuroprotective effect were regulated by NO. Hypoxia increased NO production as well as EpoR expression, and inhibition of NOS activity reduced the proportion of EpoR-expressing neurons induced at low pO2. Conversely, addition of NO donor to cultures grown under normoxia induced EpoR. Similarly, NO donor increased EpoR promoter activity in a reporter gene assay, suggesting that NO regulates EpoR at the transcription level. Preincubation of neurons with NO results in induction of EpoR, which gives rise to protection against hypoxia even in the absence of exogenous Epo, although at high concentration NO is toxic. These data provide evidence of a role for NO in Epo activity in brain and suggest links between NO production, EpoR expression, and Epo signaling in neuroprotection. Published 2010 Wiley-Liss, Inc.